Математические модели систем автоматического управления производительностью парогенератора - Никулина, Е. Н. (НТУ "ХПИ", 2010)
Приведена структурна схема системи автоматичного керування продуктивністю парогенератора. Обчислені значення постійних параметрів математичних моделей систем автоматичного керування парогенератора. Розроблені математичні моделі систем автоматичного керування продуктивністю з різними регуляторами.

The block diagram of automatic system control of the steam generator output is resulted. Values of constant parameters of mathematical models of automatic systems control of the steam generator output are calculated. Models of automatic systems control of output are developed with various regulators.
Keywords: системы автоматического управления; САУ; регулятор производительности; исполнительный механизм; питательный турбонасос; подогреватель высокого давления; mathematical models; automatic systems control